Pengaruh Penyaluran Dana Zakat Produktif Terhadap Pendapatan Mustahiq Pada Lembaga Manajemen Infaq Perwakilan Jawa Timur Di Surabaya - Rahayu, Dea Putri; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2021)
One of the economic problems in society is low income. Economic problems in society often show negative impacts on social life such as poverty, unemployment, so that it can have an impact on low education levels and low income. One of the ways to overcome the problem of poverty is by means of zakat and waqf which are the teachings that exist in Islam as contained in the letter Al-Baqarah: 43. The potential for zakat in Indonesia is quite large in the economy of the people. Based on BAZNAS research, the national zakat potential reaches IDR 217 trillion. This study aims to determine the distribution of productive zakat funds made by the Infaq Management Institute and its effect on mustahiq income. This study uses a quantitative approach. The results showed that the variable productive zakat funds had a positive and significant effect on the mustahiq income variable.